2011
DOI: 10.1093/jjco/hyr182
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Breast Cancer Risk: An Evaluation Based on a Systematic Review of Epidemiologic Evidence Among the Japanese Population

Abstract: Objective:We reviewed epidemiological studies on breastfeeding and breast cancer among Japanese women. This report is part of a series of articles written by our research group, whose aim was to evaluate the existing evidence concerning the association between healthrelated lifestyles and cancer. Methods: Original data were obtained from MEDLINE searches using PubMed or from searches of the Ichushi database, complemented by manual searches. Evaluation of associations was based on the strength of evidence and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
3
13
1
Order By: Relevance
“…The association between breastfeeding and BC remains unclear in western populations [16,17].We observed no protective association between total duration of breastfeeding and BC risk in either rural or urban women in our population. A similar observation of no association was reported in a recent systematic review of Japanese studies [18]. Breastfeeding is a universal practice in India, with a very high prevalence of 96 % in both urban and rural areas [19].…”
Section: Discussionsupporting
confidence: 76%
“…The association between breastfeeding and BC remains unclear in western populations [16,17].We observed no protective association between total duration of breastfeeding and BC risk in either rural or urban women in our population. A similar observation of no association was reported in a recent systematic review of Japanese studies [18]. Breastfeeding is a universal practice in India, with a very high prevalence of 96 % in both urban and rural areas [19].…”
Section: Discussionsupporting
confidence: 76%
“…Differences in the timing and measurement of breast density between these diverse studies are the most likely explanation for their disparate associations, though this could also be due to basic differences in the study populations. Although breast-feeding has been thought to produce an overall protective effect against breast cancer (e.g., [37]), many studies find no association (e.g., [22]) and recent systematic reviews of the topic fail to support an association (e.g., [38, 39]). More research is needed in the area of breast-feeding and breast health to better elucidate whether a protective effect exists, and if so, when and how breast-feeding might affect breast density.…”
Section: Discussionmentioning
confidence: 99%
“…A report from Japan also confirmed that breastfediing had decreased the risk of breast cancer by a large extent (18). In addition to many health advantages for babies, breastfeeding also prevents many severe diseases such as breast cancer in mothers (19).…”
Section: Introductionmentioning
confidence: 93%
“…The number of children who had given birth, continuous breastfeeding and duration of breastfeeding were also studied as to whether they had had any possible effect on breast cancer (13)(14)(15)(16)(17)(18). A decreased risk of breast cancer by 38% in women who had been continously breastfeeding in addition to a remarkable decrease with longer lasting lactation were reported by Yoo et al (14).…”
Section: Introductionmentioning
confidence: 99%